Asuhan Kebidanan Continuity Of Care (COC) Pada Ibu Hamil, Bersalin, Bayi Baru Lahir Dengan Labiopalatoschisis, Nifas Dan Keluarga Berencana Pada Ny. D Di BPM Supini Dusun Xi Desa Tanjung Rejo Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Sumiarseh1; Risda Girsang; Siti Aminah; Nurhamidah; Dewi Irawani; Lisa Putri Utami Damanik; Lusiatun (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2021)
Birth and pregnancy are physiological things, but if they are not managed properly they will become pathological. Continuity of care in midwifery is a series of continuous service activities starting from pregnancy, childbirth, postpartum, newborn and family planning services. The goal is to provide continuous care for Mrs. D at the Primary Clinic R Tarigan. The research design used is descriptive and the type of research is case study. The results showed that the care given to Mrs. D starting from pregnancy, childbirth, postpartum, and newborns went smoothly and the mother and baby were in normal condition. In conclusion, after being given continuity of care, the condition of the mother and baby was normal Suggestions for health workers, can improve and even improve the quality of services in providing midwifery care on an ongoing basis. The type of this research is a Case Study with Midwifery Care Management for Pregnant, Maternity, Postpartum, BBL and Family Planning on Ny. D at the Supini Clinic July 2020-June 2021 Conclusion: after midwifery care was carried out on Mrs. D from pregnancy to the use of family planning (KB) there was no theoretical gap with the mother’s condition